1980
DOI: 10.1073/pnas.77.5.2636
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the synthesis of glutamine synthetase by the PII protein in Klebsiella aerogenes.

Abstract: Certain mutations at the glnB locus result in the failure to fully derepress glutamine synthetase [L-glutamate:ammonia ligase (ADP-forming), EC 6.3.1.2] and to convert it to the active nonadenylylated form in response to nitrogen limitation. In these mutants the P11 regulatory protein is altered such that it cannot be converted by uridylyltransferase to the form stimulating deadenylylation of glutamine synthetase by adenylyltransferase. Additional mutations as well as insertions of transposon Tn5 at the gInB s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 20 publications
3
40
0
Order By: Relevance
“…In agreement with the regulation of ammonia assimilation which is described above and generally accepted, Foor et al (1980) showed that in a Klebsiella aerogenes glnB transposon-insertion mutant, the rate of GS-AMP deadenylylation after removal of ammonia was strongly decreased when compared to the wild type. The same was found in a Klebsiella pneumoniae glnB insertion mutant (W. C. van Heeswijk, and D. Molenaar, unpublished).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…In agreement with the regulation of ammonia assimilation which is described above and generally accepted, Foor et al (1980) showed that in a Klebsiella aerogenes glnB transposon-insertion mutant, the rate of GS-AMP deadenylylation after removal of ammonia was strongly decreased when compared to the wild type. The same was found in a Klebsiella pneumoniae glnB insertion mutant (W. C. van Heeswijk, and D. Molenaar, unpublished).…”
Section: Introductionsupporting
confidence: 88%
“…The fact that this dependence was incomplete (Foor et al, 1980) suggests the existence of a second P II protein in this closely related organism, albeit with a lower activity than the GlnK protein described in this study.…”
Section: Discussionmentioning
confidence: 57%
“…The product of glnB was finally identified as P II by Foor et al, who showed that in the original K. aerogenes glnB mutant, P II was altered so that it could not be uridylylated in nitrogenlimited conditions and consequently could not stimulate dead-enylylation of GS by Atase (64,65). A second class of glnB mutations resulted in loss of P II , and these glnB null mutants were still able to adenylylate and deadenylylate GS, although the rates of these reactions were reduced.…”
Section: Historical Perspectivementioning
confidence: 99%
“…The figure is modeled after a portion of Fig. 8 of reference 41. consequently prevent the expression of the Ntr regulon (3,4,6,10,11,19,20). Suppressor mutations that restore expression of the Ntr regulon have been found in ginL, ginB, and ginG (6,11,19,20,33,43).…”
mentioning
confidence: 99%
“…8 of reference 41. consequently prevent the expression of the Ntr regulon (3,4,6,10,11,19,20). Suppressor mutations that restore expression of the Ntr regulon have been found in ginL, ginB, and ginG (6,11,19,20,33,43). Previous results have suggested that the suppressor mutations in glnL and ginB affect the NRII-PI phosphatase activity, whereas the suppressor mutations in glnG result in altered NRI proteins that are able to activate glnA and Ntr expression in the absence of phosphorylation or that activate transcription much more efficiently than does wild-type NR,-phosphate after infrequent phosphorylation by other cross-talking cellular kinases (29).…”
mentioning
confidence: 99%